2022
DOI: 10.3390/ijerph19041943
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Year Urbanization Trajectories and Obesity in Modernizing China

Abstract: The effects of long-term urbanization changes in obesity are unclear. Data were obtained from the China Health and Nutrition Survey (CHNS) 1989–2018. A multidimensional urbanicity index was used to define the urbanization level for communities. Group-based trajectory modeling was used to identify distinct urbanization change trajectories. Gender-stratified multilevel models were used to investigate the association between urbanization trajectories and weight/BMI, through the PROC MIXED procedure, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In addition, some other studies have reported high obesity rates among indigenous or minority populations in transition from traditional to modern lifestyles (25) . This transition among minority populations was similar to the nutritional and lifestyle transition and subsequent increasing obesity among the entire Chinese population during urbanisation, as revealed by the China Health and Nutrition Survey (26) . However, urbanisation among minority groups happened later and grew slower than that in Han people, a result of the lower proportion of urban residents in ethnic autonomous regions than other Han-dominated provinces in China (8) .…”
Section: Discussionsupporting
confidence: 69%
“…In addition, some other studies have reported high obesity rates among indigenous or minority populations in transition from traditional to modern lifestyles (25) . This transition among minority populations was similar to the nutritional and lifestyle transition and subsequent increasing obesity among the entire Chinese population during urbanisation, as revealed by the China Health and Nutrition Survey (26) . However, urbanisation among minority groups happened later and grew slower than that in Han people, a result of the lower proportion of urban residents in ethnic autonomous regions than other Han-dominated provinces in China (8) .…”
Section: Discussionsupporting
confidence: 69%
“…Affluent nations like Singapore and Japan potentially attribute their significant contributions to high-income levels [ 23 ], while the high prevalence of obesity in Middle Eastern countries such as Turkey, Israel, Saudi Arabia, Iran, and Lebanon significantly factors into their research output [ 26 ]. In swiftly urbanizing nations like China, escalating obesity rates are seemingly in sync with the pace of urbanization [ 27 ], with eastern regions outpacing western ones, reflecting economic disparities. Eastern China, home to several developed provinces or cities such as Taiwan, Shanghai, Guangdong, Beijing, and Jiangsu, along with prestigious universities and hospitals, is better equipped for advanced studies and technological exploration [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of Indonesia's Sulawesi Province using built-up data from GHSL finds urbanization unfolding outside areas officially designated with implications not only for the provision of municipal services but also the potential to misclassify relevant aspects of the health and well-being [35]. A recent study in China that evaluated urbanization trajectories found a higher risk of being overweight and obese among men in areas with more urbanized features with no differences observed among women by urbanization trajectories [36]. As urbanization proceeds in Indonesia, it is expected that built-up percentages will increase much more than the 6%-point change we observed in the past which poses an increased risk of overweight and obesity over time.…”
Section: Plos Global Public Healthmentioning
confidence: 99%